Maximum systolic speed of high average cerebral artery in fetus without anemia: positive false? - Huertas, Erasmo (2020)
Severe fetal anemia can be detected in utero through the measurement of the maximum systolic velocity of the Middle Cerebral Artery (VSmax-MCA). The false positive rate of this measurement technique is unfortunately high (34%), which is why the maternal-fetal clinical correlate is suggested and conditions that falsely elevate the SPV are ruled out before making any decision regarding the diagnosis of fetal anemia. We present a case of a fetus with altered VSmax-ACM above 1.5 MoM who was born with normal hemoglobin values.